Is the association with fiber from foods in colorectal cancer confounded by folate intake? - Bingham, SA; Norat, T; Moskal, A; Ferrari, P; Slimani, N; Clavel-Chapelon, F; Kesse, E; Nieters, A; Boeing, H; Tjønneland, A; Overvad, K; Martinez, C; et al. (2005)
The effect of multivariate adjustment including folate on the strong protective effect of fiber in foods on colorectal cancer risk in the European Prospective Investigation into Cancer and Nutrition was investigated in 1,721 cases identified in the latest follow-up. The inclusion of an additional 656 cases confirmed our previously published results, with a strong and significant reduction in colorectal cancer risk of ∼ 9% for each uncalibrated quintile increase in fiber (P linear trend < 0.001) compared with an 8% reduction in our previous report, which had not been adjusted for folate. Inclusion of the other covariates (physical activity, alcohol, smoking, and red and processed meat) confirmed this significant inverse association for colon cancer and strengthened the association with left-sided colon cancer (P < 0.001). After maximum adjustment, the association between fiber and rectal cancer was not significant, as in our previous analysis. The association with fiber from different food sources was analyzed, but again, there were no significance trends after maximum adjustment. Copyright © 2005 American Association for Cancer Research.